Efficacy and Safety of First-Line Nivolumab Plus Ipilimumab in Patients with Postoperative Recurrent and Inoperable Non-Small Cell Lung Cancer: A Real-World Retrospective Observational Study - Yuhei Kurata; Atsuto Mouri; Hisao Imai; Satoshi Endo; Kasumi Tsukamoto; Kenji Masaki; Kosuke Hashimoto; Yu Miura; Ayako Shiono; Ou Yamaguchi; Junichi Nakagawa; Kyoichi Kaira; et al. (Medicina)
Background and Objectives: The comparative efficacy and safety of nivolumab plus ipilimumab (Nivo-Ipi) combination therapy between patients with either postoperative recurrent non-small cell lung cancer (NSCLC) or inoperable stage III/IV NSCLC have yet to be conclusively determined. Materials and Methods: This retrospective study reviewed the medical records of consecutive patients diagnosed with either postoperative recurrent NSCLC or inoperable stage III/IV NSCLC. Both groups, referred to as the postoperative and inoperable cohorts respectively, underwent Nivo-Ipi therapy at four Japanese medical institutions between December 2020 and November 2022. The study’s primary aim was to evaluate and compare the efficacy and safety outcomes across these two groups. Results: A total of 161 patients received Nivo-Ipi therapy (postoperative group, n = 30; inoperable group, n = 131). The objective response rate was comparable between the postoperative and inoperable groups (36.7% vs. 32.1%, p = 0.67). Median progression-free survival did not differ significantly between groups (8.9 months vs. 6.5 months, p = 0.14). However, median overall survival was significantly longer in the postoperative group (not reached vs. 13.0 months, p = 0.012). The incidence of grade ≥ 3 adverse events in the postoperative group included lung injury (13.3%), liver dysfunction (10.0%), adrenal insufficiency (6.7%), and colitis (6.7%). No significant difference was observed in the frequency of grade ≥ 3 treatment-related adverse events between the groups, and no treatment-related deaths occurred in the postoperative group. Conclusions: Patients with postoperative recurrent NSCLC treated with Nivo-Ipi demonstrated significantly longer overall survival compared to those with inoperable NSCLC. Given its favorable efficacy and acceptable toxicity profile, postoperative recurrent disease may warrant consideration as a stratification factor in clinical trials for advanced NSCLC. Nivo-Ipi therapy could serve as a preferred first-line treatment option for patients with postoperative recurrent NSCLC.